PENYELESAIAN WANPRESTASI PERJANJIAN KREDIT KELOMPOK PRODUKTIF DENGAN JAMINAN DI CU KELING KUMANG DI KABUPATEN SINTANG - Tri Minarti (Universitas Kapuas Sintang, 2022)
This study is intended to investigate the settlement of productive group Credit agreement defaults through collateral at CU Keling Kumang of Sintang Regency. This study designed as a form of juridical sociological method with descriptive analysis in nature. The technique for collecting data used a field research (interview) and a literature study are intended to find the appropriate sources based on rules as regulated. Therefor, this study is drived to analyse sistematically with quantitative method.In conclusion, a member meeting is the strategy used by CU. Keling Kumang for finding solution. The strategy are providing a subpoena, extending the loan term, and converting group loans into individual loans. Payments are made to each member to settle defaults on productive group credit agreements with guarantees at CU. Keling Kumang. It is truly through an alternative way to negotiate between CU parties (Keling Kumang and members of the Productive Group) outside the court. This study provide several suggestion, namely: firstly, the settlement of theproductive group’s credit agreement default settlement with guarantees at CU. Keling Kumang. Secondly, the guarantees should be included in the loan agreement. Finally, if the settlement cannot be resolved outside the court, then the CU Keling Kumang in Sintang Regency can take legal action.Keywords: Settlement , Defaults, Guarantees